1998
DOI: 10.1007/s11745-998-0273-z
|View full text |Cite
|
Sign up to set email alerts
|

A new conjugated linoleic acid isomer, 7 trans, 9 cis‐octadecadienoic acid, in cow milk, cheese, beef and human milk and adipose tissue

Abstract: The identity of a previously unrecognized conjugated linoleic acid (CLA) isomer, 7 trans, 9 cis-octadecadienoic acid (18:2) was confirmed in milk, cheese, beef, human milk, and human adipose tissue. The 7 trans, 9 cis-18:2 isomer was resolved chromatographically as the methyl ester by silver ion-high-performance liquid chromatography (Ag+-HPLC); it eluted after the major 9 cis, 11 trans-18:2 isomer (rumenic acid) in the natural products analyzed. In the biological matrices investigated by Ag+-HPLC, the 7 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
4
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 30 publications
5
114
4
1
Order By: Relevance
“…A very recent study confirmed the properties of CLA to limiting the extent of body fat stores in man [113]. From a quantitative point of view, the principal types of CLA produced by rumen microorganisms are ∆9 cis-∆11 trans as well as ∆10 trans-∆12 cis [40] and ∆7 trans-∆9 cis [129] and to a lesser extent, their trans-trans isomers ∆9-∆11 and ∆10-∆12 [40]. The minor forms are represented by cis-trans isomers in positions 7-9, 8-10, 11-13, and 12-14 and by trans-trans isomers in positions 8-10 and 11-13 [40].…”
Section: Meat Lipids: Dietetic Aspectsmentioning
confidence: 81%
“…A very recent study confirmed the properties of CLA to limiting the extent of body fat stores in man [113]. From a quantitative point of view, the principal types of CLA produced by rumen microorganisms are ∆9 cis-∆11 trans as well as ∆10 trans-∆12 cis [40] and ∆7 trans-∆9 cis [129] and to a lesser extent, their trans-trans isomers ∆9-∆11 and ∆10-∆12 [40]. The minor forms are represented by cis-trans isomers in positions 7-9, 8-10, 11-13, and 12-14 and by trans-trans isomers in positions 8-10 and 11-13 [40].…”
Section: Meat Lipids: Dietetic Aspectsmentioning
confidence: 81%
“…Even though the cis9,trans11-CLA (c9,t11-C18:2) is the most abundant isomer in dairy products [1], recent research has been focused on trans10,cis12-CLA (t10,c12-C18:2), because it decreases milk fat content (MFC) in dairy cows [2]. The c9,t11-C18:2 isomer in milk originates partly from the ruminal biohydrogenation of linoleic acid, and mostly from the desaturation of the t11-C18:1 fatty acid (FA) via Δ 9 desaturase in the mammary gland [3].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature was held at 170°C for 40 min. The peak identification was carried out by comparing the reported conjugated linoleic acid profiles in references [10,11,13,14] and methyl esters prepared from the 9c11t and 10t12c triacylglycerols as described in the section ''Samples and methods''. The peaks in the chromatograms were then integrated, and their relative percentages were calculated using an excel spread sheet.…”
Section: Gas Chromatographic Analysismentioning
confidence: 99%
“…Of these, 9c11t is dominant, with about 80-90% of all the conjugated linoleic acids. The isomer 7t 9c was found in most of the dairy products as the second dominant CLA fatty acid [10]. The isomer 9c11t is also thought to be the most biologically active [1,2].…”
Section: Introductionmentioning
confidence: 99%